Degradation of Chrysene by Enriched Bacterial Consortium - Vaidya, Sagar; Devpura, Neelam; Jain, Kunal; Madamwar, Datta (Frontiers in Microbiology, 2018)
Chrysene is a high molecular weight (HMW), polycyclic aromatic hydrocarbon (PAH) known for its recalcitrance and carcinogenic properties and sparsely soluble (0.003 mg/L) in aqueous medium. Due to these refractory properties, bioavailability of chrysene is very low and therefore is persistence in the environment escaping the metabolism by microorganisms. However, few bacterial and fungal strains are reported to degrade chrysene, but with lower efficiency, requiring additional/extraneous carbon sources (co-substrates) for it’s complete mineralization. In this study, development, enrichment and characterization of bacterial consortium ASDC, consisting of Rhodococcus sp., ASDC1; Bacillus sp. ASDC2 and Burkholderia sp. ASDC3 were reported. Chrysene was utilized as a sole source of carbon and energy by the consortium, having maximum degradation rate of 1.5 mg/L/day and maximum growth rate of 0.125/h, under optimized conditions of pH 7.0, 37°C under aeration of 150 rpm on gyrating shaking. Chrysene degradation was unaffected in presence of other PAHs like pyrene, fluoranthene, naphthalene, phenanthrene, benzene, toluene and xylene, individually as well as in mixture. The results revealed that peptone, ammonium nitrate, sodium succinate have enhanced the chrysene degradation rate during first 24 h of experimentation, which was later on inhibited with increase in incubation time. The chrysene degradation was inhibited by mercury even at lower concentration (1mM). The results also revealed that SDS has enhanced its degradation by 5.2 folds for initial 24 h of growth, but with increasing in the incubation period, it decreases by 1.2 fold on 7th day experimentation. The HPLC studies suggested that chrysene was degraded through phthalic acid pathway by the consortium ASDC and the stoichiometric measurements indicated the complete mineralization of chrysene. The flask scale results were validated at simulated microcosm models, where enriched consortium ASDC exhibited maximum degradation (96 %) in polluted, non-sterile soil sediment, indicating that consortial strains along with indigenous metabolism showed synergistic metabolism for degradation of chrysene. Thus, the above study revealed the useful enrichment of bacterial community for synergistic degradation of PAHs (chrysene) which could be further exploited for in situ remediation of PAH contaminated sites.